BETWEEN LAW, THEOLOGY, AND MYSTICISM: AL-GHAZĀLĪ’S ROLE IN SHAPING MEDIEVAL ISLAMIC SCHOLARSHIP - Rajabova Sitorabonu Tohirovna (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2026)
This article explores the role of Abu Hamid al-Ghazālī (1058–1111) in shaping medieval Islamic scholarship across the fields of law, theology, and mysticism. The study examines his intellectual contributions, personal qualities, and the way medieval Muslim historians portrayed his life and work. Al-Ghazālī’s integration of jurisprudence, philosophical reasoning, and Sufi thought is analyzed, highlighting his influence on ethical, spiritual, and intellectual development in Islamic societies. The article also discusses the relevance of his legacy for understanding the interplay between religious, intellectual, and social spheres in the medieval Islamic world.